PERAN “TŌKANG TEKKU’ TĒNGKA” DALAM PENYELESAIAN SENGKETA PADA LEMBAGA ADAT DI MADURA - Muchlis (HKI IAI Miftahul Ulum Pamekasan, 2020)
(The usual alternative dispute resolution conducted by elite figures out of Court (non litigation) with different systems between the indigenous regions with one another by a mediator, in mediation in custom lemabag Madura.Dispute resolution through mediation is certainly not always manage to achieve peace, as the dispute continues, the less expert public figures acting as conciliator of the parties (the mediator). As one of the results of research carried out in the village of Palengaan author Laok against implementation of dispute resolution happening within the community.The village has a community belief system of the ditokohkan be a term